1996
DOI: 10.1007/bf01443399
|View full text |Cite
|
Sign up to set email alerts
|

An accurate Van der Waals-type equation of state for the Lennard-Jones fluid

Abstract: A new equation of state (EOS) is proposed for the Helmholtz energy F of the Lennard-Jones fluid which represents the thermodynamic properties over a wide range of temperatures and densities. The EOS is written in the form of a generalized van der Waals equation, F = FH + F^, where FH is a hard body contribution and F^ an attractive dispersion force contribution. The expression for F H is closely related to the hybrid Barker-Henderson pertubation theory. The construction of F^ is accomplished with the Setzmann-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
98
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 23 publications
17
98
0
Order By: Relevance
“…The simulation results for the saturated liquid density by Lotfi et al 8 as well as by Potoff and Panagiotopoulos 9 generally agree with the correlation by Lotfi et al 8 within their statistical uncertainties. The results from three equations of the state by Johnson et al, 10 Kolafa and Nezbeda 11 as well as Mecke et al 12 also coincide well with the correlation by Lotfi et al 8 The simulation results by Goujon et al,…”
supporting
confidence: 69%
“…The simulation results for the saturated liquid density by Lotfi et al 8 as well as by Potoff and Panagiotopoulos 9 generally agree with the correlation by Lotfi et al 8 within their statistical uncertainties. The results from three equations of the state by Johnson et al, 10 Kolafa and Nezbeda 11 as well as Mecke et al 12 also coincide well with the correlation by Lotfi et al 8 The simulation results by Goujon et al,…”
supporting
confidence: 69%
“…Here we give here later developments (Wedberg 2011;Wedberg et al 2011b) than described by Wedberg et al (Wedberg et al 2010), which has less reliable approximations for the DCF tail. Figure 6.6 compares the isothermal compressibilities obtained from the method with those obtained from the EOS of Mecke et al for LJ fluids (Mecke et al 1996). At all four temperatures, our results are qualitatively consistent with the EOS, with differences in the range of 1-5%.…”
Section: Model Fluidssupporting
confidence: 71%
“…Its advantages of minimal computational effort and limited need for case-by-case judgment in analysis indicate its efficiency and robustness. (Mecke et al 1996) are also shown. …”
Section: Discussionmentioning
confidence: 99%
“…3). The extrapolated h(r) integrates to ρk B T κ T = 0.055, ∼2% from the Mecke et al 60 equation of state value of 0.056. This shows that via the extrapolation method, accurate properties can be obtained from simulations of small systems, avoiding the extra computational efforts that larger systems require.…”
Section: Errors Due To Finitenessmentioning
confidence: 99%